Comparison of three multiplex gastrointestinal platforms for the detection of gastroenteritis viruses - Chhabra, Preeti (J Clin Virol, 2017)
BACKGROUND: Viruses are major etiological agents of childhood gastroenteritis. In recent years, several molecular platforms for the detection of viral enteric pathogens have become available. OBJECTIVE/STUDY DESIGN: We evaluated the performance of three multiplex platforms including Biofire’s Gastrointestinal Panel (FilmArray), Luminex xTAG(®) Gastrointestinal Pathogen Panel (GPP), and the TaqMan Array Card (TAC) for the detection of five gastroenteritis viruses using a coded panel of 300 archived stool samples. RESULTS: The FilmArray detected a virus in 199 (96.1%) and the TAC in 172 (83.1%) of the 207 samples (187 samples positive for a single virus and 20 samples positive for more than one virus) whereas the GPP detected a virus in 100 (78.7%) of the 127 (97 positive for one virus and three positive for more than one virus) samples. Overall the clinical accuracy was highest for the FilmArray (98%) followed by TAC (97.2%) and GPP (96.9%). The sensitivity of the FilmArray, GPP and TAC platforms was highest for rotavirus (100%, 95.8%, and 89.6%, respectively) and lowest for adenovirus type 40/41 (97.4%, 57.9% and 68.4%). The specificity of the three platforms ranged from 95.6% (rotavirus) to 99.6% (norovirus/sapovirus) for the FilmArray, 99.6% (norovirus) to 100% (rotavirus/adenovirus) for GPP, and 98.9% (astrovirus) to 100% (rotavirus/sapovirus) for TAC. CONCLUSION: The FilmArray demonstrated the best analytical performance followed by TAC. In recent years, the availability of multi-enteric molecular testing platforms has increased significantly and our data highlight the strengths and weaknesses of these platforms.